O efeito do pH na interação da albumina sérica humana e os flavonoides quercetina e quercitrina - Lopez Ayme, Alvaro Jhovaldo [UNESP] (2014)
The flavonoids are poliphenolic compounds found in plants, which are responsible to provide pigmentation and in some cases act as an inhibitors of infections mediated by microorganism. Recently, their role as an antioxidant and in the regulation of signaling mechanism have been discovered, reason by which the research with flavonoids have grown. An important protein, which is found in the human plasma is the Human Serum Albumin (HSA), which is responsible to transport the nutrients (ligands) found in the blood to show them to cells and tissues. The process by which the HSA give off the ligand to cell is called delivery. In the delivery process, it is hope that the strenght of the Flavonoid-HSA complex is weakened, causing the delivery of the ligand. Due to the strenght of the Flavonoid-HSA complex could be weakened by a physiological factor such as pH, is that in the present work is studied the effect of the pH on the interaction between HSA and the flavonoids Quercetin and Quercitrin. In order to determine the role of the pH as a modulator of flavonoids delivery, this work will explore, i) the quenching constants, ii) thermodynamic parameters such as enthalpy (ΔHo), entropy (ΔSo) and the Gibbs free energy (ΔGo), iii) the number of binding sites and iv) FRET of the Quercetin-HSA and Quercitrin-HSA complexes in the pH range from 7.0 to 6.0. From the fluorescence quenching data at pH 7.0, was observed that the Quercetin-HSA interaction was described by the Perrin model, while the Quercitrin-HSA complex was described by the linear Stern-Volmer model. The quenching models were the same at pH 6.0. At a slightly acidic pH the fluorescence quenching constants of the Quercetin-HSA showed to decrease, while for the Quercitrin-HSA complexes increased. From the fluorescence quenching studies at different temperatures (288, 298 and 308K) it was showed that the quenching mechanisms for both flavonoids (Quercetin and Quercitrin) are static ...